Setting Boundaries at Borders Reconciling Laptop Searches and Privacy. - Power, E.M (IEEE Security and privacy : building confidence in a networked world)
If you've traveled internationally on business, the odds are that you've taken your laptop with you. Like most business travelers, you need these ubiquitous devices to do work, make presentations, and communicate with coworkers, family, and friends via the Internet. In a previous department, we explored the notion that laptops deserve special consideration because of the increasingly blurred line between home and office, the entrusting of intimate, private information to storage on laptops, and the resulting need to rethink the rules surrounding reasons-able expectations of privacy. This time, we examine the nexus between laptops, a government's search and seizure powers, and a traveler's transit through an international border checkpoint where customs officials have enhanced powers to search travelers and their belongings